The Strength Of Legal Deed Auction Summary Of Burdened Of Confiscation Based On Regulation Of Finance Minister Number 27 / Pmk.06 / 2016 In The City Of Semarang - Ferry Setiawan Setiawan; Yanto Risdianto; Soegiyanto Soegiyanto (Jurnal Akta, 2020)
The purpose of this study was to: 1) To Know the Auction for Goods burdened Confiscation Based Finance Minister Regulation No. 27 / PMK.06 / 2016 in the city of Semarang. 2) To know the Power of Law Treatise Deed Auctions for Goods burdened Confiscation Based Finance Minister Regulation No. 27 / PMK.06 / 2016 in the city of Semarang. The data used in this study are primary data and secondary data and data that can support tertiary study, which was then analyzed by normative juridical method.Based on the results of data analysis concluded that: 1) How the Auction of Goods Seized Burdened By Finance Minister Regulation Number 27 / PMK.6 / 2016 in Semarang. In the official auction assisted by guides who guilty of employees DJKN, the auction progresses No offers the winning auction is bidders who bid the highest. Each implementation of the auction will be charged Customs Auction accordance with government regulations governing the types and rates of non-tax state revenue. Payment of the auction price and Customs Auction shall be made in cash or check or checking account, no later than five (5) working days. In the case of submission of official documents of the auction must submit the original document of title or goods are auctioned off to the buyer or winning bidder no later than 1 (one) working day. Buyers must show proof of payment of the form and submit proof of deposit Tax on Acquisition of Land and Building If items such as land and buildings. 2) How the Legal Power of The Minutes of the Auction the Seized Goods Burdened By Finance Minister Regulation Number 27 / PMK.6 / 2016 in Semarang. Deed Auctions treatise consists of body deed, deed and leg mid deed which contains about the day, date, type of goods, address of the seller, as well as goods sold. Minutes of Deed Auctions is an authentic deed made by officials of the auction and use the laws and legislation so this auction treatise deed has permanent legal force if there are problems in the future.Key Words: The Power of Law; the Deed of Auction; Goods Burdened Confiscation.